Persepsi Nasabah terhadap Penerapan Sistem Layanan Produk dan Jasa E-Banking - SUHARINI, MIEKE (UI Scholars Hub, 2010)
This research analyzes the customer's perception towards the application of e-banking service system applied by Bank Mandiri, starting from the end of the year 2005. The respondents of this research are Bank Mandiri Costumers living in Jakarta. This research used quantitative approach. The result shows that the majority of the respondents generally gave a positive response towards the indicators used in this research. Even so, some indicators, such as responsiveness, promotion, product variety, and information intake for the customers, are still not seen in particular by the respondents. This means the majority of bank customers in Jakarta think that the quality of Bank Mandiri’s e-banking system and products are good, even though there may be some weaknesses in some fields. As a whole, there is a different perception of the customers toward what they want and what they get.